PERAN KEADILAN PROSEDURAL, KEPERCAYAAN, KEPUASAN KERJA DAN KOMITMEN ORGANISASI DALAM MENINGKATKAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) (Studi pada Karyawan PDAM Kabupaten Demak) - Anggraini, Marshellani Madya; Rahardjo, Mudji (Faculty of Economics and Business Diponegoro University, 2016)
The existence of Organization Citizenship Behavior (OCB) is believed can bring positive impact not only for the members but also give a contribution to the organization itself. Therefore many organizations improve their OCB to their employer. This research aimed to examine the impact of procedural justice, trust, job satisfaction and organizational commitment on OCB. The research was conducted in Perusahaan Daerah Air Minum (PDAM) Demak regency which is one of BUMD. There are 126 employers as research sample. The instrument of questioner is used to get the research data. Multiple regression analysis is used to test the impact those variables on the OCB. The result shows that procedural justice, trust, job satisfaction and organizational commitment have positive and significant influence to the Organizational Citizenship Behavior (OCB). Organizational commitment is a variable which affected the most while procedural justice has the weakest effect.